Relationship between processing information skills and academic performance - Miljánovich Castilla, Manuel (2005)
The correlative coefficients evaluated between the total and partial scores on an elaborative processing of information skills test and the averages notes corresponding to four academic semesters from a students sample of San Marcos University's diverse faculties, allow us to sustain, according to the hypotesis stated, that those skills have an apreciable predictive power of succes in university studies, specially in humanity area. The survey included a comparison betwen the reported correlation and the located, on the same sample, between scores on the admision university test and the averages notes. The result shows in general, that the prosecution of the information test, have a larger predictive power than the admision test.